Synthesis and Reactions of 3-Formyl-1-Phenyl-5-[2-Thiazolo) Monoazamethine] Pyrazole - Kamel Khalafallah, Ali (Asian Journal of Chemistry, 2012)
3-Formayl-1-phenyl-5-[(2-thioazolo) monoazamethine] pyrazole was condensed with acetophenone and acetophenone derivatives. The resulting α,β-unsaturated ketonic system was condensed with hydrazines, hydroxylamine, urea and thiourea affording isolated pyrazolines, isoxazolines, pyrimidines and/or pyrimidine-thione derivatives.